Analisis faktor-faktor yang mempengaruhi motivasi penyuluh pertanian di era revolusi industri 4.0 - Sugino Sugino (Fakultas Pertanian Universitas Yudharta Pasuruan, 2021)
The motivation of agricultural instructors can be influenced by driving factors, inhibiting factors, external factors, and instructor competency factors. This study aims to analyze the factors of work motivation in the industrial revolution 4.0 era. The research chose Batu City, Malang City, and Malang Regency as study areas. The population is all extension workers who have civil servant status, whether the skilled or expert level in the study area, as many as 149 instructors. Determination of the sample using the Slovin formula with a confidence level of 10% which resulted in 98 respondents and was selected by purposive sampling. Primary data collection in the form of a survey for respondents who produced interval data on a Likert scale. Achievement analysis supports the path analysis supported by the SPSS Version 21 application in completing its statistical calculations. The study found that the driving factors and inhibiting factors did not directly influence the motivation of the instructor. While external factors and competency factors have a direct influence on instructor motivation.